Bioinspired Underwater Superoleophobic Microlens Array With Remarkable Oil-Repellent and Self-Cleaning Ability - Bian, Hao; Liang, Jie; Li, Minjing; Zhang, Fan; Wei, Yang (Frontiers in Chemistry, 2020)
Underwater superoleophobic microlens array (MLA) has been emerging as a crucial device for its wide applications in ocean optical imaging and sensing, endoscopic surgery, microfluidics and optofluidics, and other biomedical applications. Fabrication of microlens arrays integrated with excellent optical performance as well as underwater superoleophobicity remains a great challenge. In this paper, we report an underwater super oil-repellent MLA on a transparent optical glass substrate via femtosecond laser-induced phase and structural modification and chemical isotropic etching. The fabricated sample simultaneously possesses microlens structures with a smooth surface to enable optical imaging function, and grid-patterned biomimetic micro/nano hierarchical surface structures to produce underwater oil-resistance with a contact angle of 160.0°and a sliding angle of 1.5°. The resultant oil-repellent MLA exhibits underwater superoleophobicity and self-cleaning abilities in water. Meanwhile, it was demonstrated to have impressive imaging capability even after oil contamination. We believe that this novel resultant anti-oil MLA will be helpful for underwater detection and bioscience research, especially in oil polluted underwater workspaces.